Satellite based estimation of land cover change and soil degradation in Urgamal, Durvoljin, Erdenekhairkhan soums of Zavkhan province (Journal of Applied Science and Engineering A, 2023)
In this research, climate change over the last 22 years (2000-2022) in Durvoljin, Ugramal and Erdenekhairkhan Sum areas of Zavkhan province was determined and desertification status was assessed using satellite data. In this research, the soil-adjusted vegetation index (SAVI) was calculated among the vegetation indi-ces. When SAVI is calculated using data from the red and NIR channels of the MODIS satellite data, SAVI values vary between -0.4 and +0.5 as a result of im-age processing. The spatial heterogeneity of the land surface of the study area was mapped by SAVI values from -0.4 to +0.02 for water, +0.02 to +0.08 for gravel and rock, +0.08 to +0.11 for sand, +0.11 to +0.16 for sparse soil, +0.16 from - to +0.23 with sparse vegetation, and between +0.23 and +0.5 with good vegetation in 6 categories. As a result of the study, SAVI proved to be more suitable for determining soil types in desert and semi-desert areas.